Development and evaluation of a family-child reading picture book on reducing autism spectrum disorder caregivers’ psychological stress: a mixed method study - Yang, Lei; Ye, Jinlin; Zhu, Hongrui; Tang, Yao; Li, Xianhong (Frontiers in Psychiatry, 2024)
Introduction The rapid increasing prevalence of ASD has become a significant global health issue. Caregivers of children with ASD are experiencing higher level of psychological stress and mental disorders. However, interventions to improve the psychological health of caregivers of children with ASD have largely been neglected. Methods Based on the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model, we initially did in-depth interviews with 8 caregivers, and conducted field observation in two rehabilitation centers to analyze the daily lives, the empowered components, the emotional moments of the children with autism and their caregivers. Then we designed the outline of the picture book, and developed it by a multi-disciplinary team by 4 rounds. After that, this picture book was sent out to 54 caregivers of children with ASD for family-child reading in one month. A quantitative questionnaire was administered before and after their reading to evaluate the efficacy of reducing their stress and affiliate stigma, and improving self-efficacy, resilience, empowerment capacity; and exit interviews were conducted after their initial reading to assess the acceptability, content appropriateness, perceived benefits and generalizability of this picture book. Quantitative data were analyzed by descriptive analysis and paired t-tests using IBM SPSS 26.0. Qualitative data were analyzed using template analysis. Results In total, 54 caregivers read the picture book with their child, with the total of 149 (an average of 2.76 per family) times reading in one month. Among them, 39 caregivers returned the following-up questionnaires. Although most of the outcome measures did not showed significant changes except the stress level decreased statistically significant (13.38 ± 3.864 to 11.79 ± 3.238, P=0.001), caregivers reported that the picture book echoed their daily lives and gave them a sense of warmth, inspiration, and hope, as well as some insight on family relationships and attitudes towards the disorder. They also expressed a willingness to disseminate the book to other families with children suffering ASD and the public. Conclusion This specially designed picture book has been proven to be an acceptable, content-appropriate, and effective family-centered psychological intervention, which could be easily scaled up.